Implementation of the posbindu PTM program by community nurses in early detection of diabetes and hypertension in rural villages - Minanton Minanton; Nuridha Fauziyah; Habsyah Saparidah Agustina; Novian Mahayu Adiutama; Wardah Fauziah; Achmad Vindo Galaresa; Leli Rezky Dwi Oktavia; Bayu Nirwana (Politeknik Negeri Subang, 2026)
Background: The increasing prevalence of non-communicable diseases (NCDs), particularly diabetes mellitus and hypertension, poses a significant health challenge in Indonesia. Early detection through Posbindu PTM (Integrated Non-Communicable Disease Health Post) is essential to prevent complications. Community nurses play a vital role in organizing and sustaining this program, especially in rural and remote regions such as Subang Regency, West Java. Purpose: To describe the implementation of the Posbindu PTM program by community nurses in the early detection of diabetes and hypertension in rural villages within the Kalijati Health Center area, Subang Regency, West Java. Methods: This quantitative descriptive study involved 90 adult participants aged 18 years and older who attended Posbindu PTM activities at Kalijati Health Center, Subang Regency, West Java, between January and March 2024. Data were collected through structured questionnaires and secondary data from screening records. Descriptive analysis was performed using SPSS version 27, focusing on coverage, participation, and outcomes of early detection activities. Of the 90 participants recruited, 82 were included in the final analysis; 8 were excluded due to incomplete data. Results: Among 82 participants, 58.9% were female and 41.1% were male, with a mean age of 47.6 years (SD = 12.3). Screening results indicated that 21.1% had elevated fasting blood glucose levels (≥126 mg/dL), and 34.4% had high blood pressure (≥140/90 mmHg). Nurse involvement in Posbindu PTM was reported as active by 82% of respondents, particularly in health education and screening. However, challenges included irregular attendance, limited diagnostic equipment, and lack of follow-up visits. Conclusion: The study highlights the crucial contribution of community nurses in detecting early-stage diabetes and hypertension through Posbindu PTM. Strengthening nurse capacity, ensuring equipment availability, and enhancing community participation are recommended to optimize program sustainability in rural areas